Faire mémoire par le trait ou les tribulations latino-américaines de Charlie - Frédérique Langue (Conserveries Mémorielles)
In an adverse context for freedom of thought in the so called public sphere (both in Europe and Latin America), this essay explores the sense that is supposed to have from Latin America one of the "recent disasters" of present times, as was the attack against the satirical newspaper Charlie Hebdo in January 2015. Political caricature appears to be the expression of a traumatic experience and a shared political culture through republican and democratic practices as well. However, on a democratized continent which is still grappling with memory and the traumatic past of dictatorships in a conflicting present-day, this imaginary is also strongly questioned by authoritarian ideological options. A figure impacts decisively on new historicity regime bounded with the end of dictatorships: the victims, yet overhelming official histories through the stigmatization of “black legend” (i.e.: spanish colonization). They not only replace "the era of witnesses" highly valued by the history of present time but also integrate an instrumentalized regime of emotions finally leading to a skewed view of history, emphasized by social networks.